Efektifitas Tanaman Refugia Kacang-Kacangan Menangkal Intensitas Serangan Hama Ulat Grayak (spodoptera exigua Hubner.) Pada Bawang Merah: Effectiveness of Bean Refugia to Prevent Intensity Attacks of Armyworm Pests (Spodoptera exigua Hubner.) On Shallots - I Ketut Ngawit; Bambang Budi Santoso; Hary Haryanto (LPPM Universitas Mataram, 2023)
This experimental research aims to obtain the type of legume refugia plant that is most effective in preventing invasion, colonization and intensity of attack by the Spodoptera exigua Hubner pest on shallot. The experiment was designed with a randomized block design consisting of six treatments of various refugia plants, namely shallot plants without refugia treatment (Ro), shallot plants with refugia treatment peanuts (R1), soybeans (R2), green beans (R3), red beans (R4) and cowpeas (R5), which are planted in two rows on the side of the bund at a distance of 10 cm from the outermost row of shallot plants. Observation parameters were egg population, larvae, intensity of S. exigua pest attack and weight of fresh shallot bulbs. The variety of refugia plants from the legume group influences invasion, colonization and the intensity of Spodoptera exigua Hubner pest attacks. on red onions. Peanut and cowpea refugia plants planted in two rows on the sides of the shallot mounds, are very effective in preventing invasion, colonization and the intensity of Spodoptera exigua Hubner pest attacks, so that the shallot plants experience very light disturbance with an attack intensity of 2,522% – 4,432 %, which is in the very low category. As a result, the yield of fresh shallot tubers obtained was significantly higher compared to shallot plants without refugia plants and with refugia plants of soybeans, green beans and red beans. Soybean, green bean and red bean refugia plants are not effective in preventing Spodoptera exigua Hubner pest attacks on shallots because the plants experience attack intensity from the age of 49 HST – 63 HST of 21.86% - 23.34% with the attack intensity being in the medium category.